EARLY DIAGNOSIS AND TREATMENT OF THE POSTERIOR URETHRAL VALVE (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Posterior urethral valves are the leading cause of urinary tract obstruction in children, associated with the risk of renal failure and bladder dysfunction. A review of the literature, including peer-reviewed sources and meta-analyses, discusses the early diagnosis and treatment of this pathology.